Fiscal Federalism and State Financial Autonomy: A Dependency Theory Analysis of Federal-State Relations in Sabah, Malaysia - Nur Syaza Salihah Jasni; Ramli Dollah (International Journal of Asia Pacific Studies, 2026)
This study analyses the influence of fiscal federalism on Sabah’s financial autonomy within Malaysia’s federal framework, using dependency theory as a perspective. The study examines how Malaysia’s centralised fiscal structure establishes a core-periphery dynamic that diminishes Sabah’s financial autonomy and developmental prospects. Despite constitutional guarantees under the Malaysia Agreement 1963 (MA63), Sabah struggles to generate revenue and manage its resources. This is especially true when it comes to oil revenues, as it receives only 5% of Malaysia’s total oil production despite contributing about 25% of the country’s output. The research examines three key facets: Sabah’s historical integration into Malaysia, the duties of MA63, and the development of intergovernmental budgetary arrangements. The research illustrates how structural dependencies sustain Sabah’s fiscal limitations through comparative analysis with other federal systems and the application of dependency theory. This study advocates for extensive reforms, encompassing: the renegotiation of revenue-sharing formulae, augmentation of state-level taxing authority, implementation of transparent equalisation methods, and the establishment of independent fiscal commissions. These ideas seek to disrupt the cycle of dependency and create a fairer budgetary relationship between federal and state governments that honours the essence of MA63 and fosters sustainable development in Sabah.